SATISFACTION MEDIATES PERCEIVED BENEFITS AND SECURITY TO TRUST - Labolong, Wityaningsih; Tombolotutu, Muzakir; Sutomo, Maskuri (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
Empirically, this study aims to analyze and explain (1) The effect of perceived benefits on customer satisfaction of  Quick Response Code Indonesian Standart (QRIS) users (2) The effect of security on customer satisfaction of Quick Response Code Indonesian Standart users (3) The effect of perceived benefits on customer trust in Quick Response Code Indonesian Standart users (4) The effect of security has a significant effect on customer trust in Quick Response Code Indonesian Standart users (6) Satisfaction mediates the effect between perceived benefits on customer trust in Quick Response Code Indonesian Standart users. (5) The effect of satisfaction on customer trust in Quick Response Code Indonesian Standard users (6) Satisfaction mediates the influence between perceived benefits on customer trust in Quick Response Code Indonesian Standard users (7) Satisfaction mediates the influence between security on customer trust in Quick Response Code Indonesian Standard users. This type of research is descriptive and exploratory, rather than causal, hypothesis testing using PLS-SEM with a sample of 170 respondents. The results of the analysis show that for testing the direct effect, hypothesis 3 is rejected, and for testing the indirect effect, all hypotheses are accepted, provided that the P-value <0.05 and the t-value> 1.97.